Peningkatan Kemampuan Menulis Artikel Ilmiah melalui Strategi Pembelajaran Berbasis Kecerdasan Verbal Linguistik - Sabitul Kirom (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2019)
The skill of writing scientific articles is an important skill mastered by every student. The activity of writing scientific articles becomes a means in training students' abilities in communicating the results of their thoughts and research. However, in reality, many students have difficulty in writing scientific articles. This study aims to improve students' abilities in writing scientific articles through learning strategies based on verbal-linguistic intelligence. This research uses a qualitative approach with the Classroom Action Research design. The data used in this research are process data and learning product data writing scientific articles using learning strategies based on verbal-linguistic intelligence. The results of this study indicate that students' abilities in writing scientific articles can be improved through learning strategies based on verbal-linguistic intelligence. Improvement of student ability can be seen in terms of the process and product of learning outcomes.